Ovitrap Index and Transovarial Transmission Rate of Dengue Virus of Male and Female Aedes aegypti Mosquitoes in Makassar, South Sulawesi, Indonesia - Isnadiyah Juhdi; Loeki Enggar Fitri; Lilik Zuhriyah; Andi Arahmadani Arasy (Journal of Tropical Life Science, 2019)
The incidence rate (IR) of dengue hemorrhagic fever (DHF) in Indonesia has increased in recent years and still causes a health problem. Makassar, as one of the big cities in Indonesia, is also experiencing of DHF cases. According to the Health Office of Makassar City, DHF cases during 2014 â€“ 2016 has increased from 139 to 250 cases. The defense mechanism of dengue virus in transovarial transmission from female mosquitoes to eggs is estimated to be one of the factors that increase the rate of DHF. In addition, the circulation of the Aedes aegypti mosquitoes can also affect the increase of the rate. This study aims are to identify ovitrap index and to find out how much the vertical transmission of dengue virus by measuring the minimum infection rate (MIR) and the distribution of four dengue virus serotype in Ae. aegypti mosquitoes in the city of Makassar, South Sulawesi, as well as their association with the incidence rate (IR) in the area. This observational research uses ecological study with cross-sectional approach. The samples of the study are male and female mosquitoes from Ae.aegypti eggs obtained from the installation of ovitrapÂ in 30 urban villages in Makassar. Dengue virus identification was performed using a reverse transcriptase polymerase chain reaction (RT-PCR). These results showed that the ovitrap index (IO) was in the range of 0 - 66.7%. The average value of the ovitrap index outside the house (44.44%) was greater than inside house (37.22%). The results of identification of dengue virus using RT-PCR showed negative results as indicated by the non-formation of a band on 75 pools male and 78 pools female Ae. aegypti mosquitoes after electrophoresis. The results of this study indicated that the Ae. aegypti mosquito in Makassar City showed a tendency to lay eggs outside the house due to the habit of the people who put rain water shelters outside the house which could become breeding place for Ae. aegypti mosquitoes. This study also showed that there was no transovarial transmission of DENV found in male and female Ae. aegypti mosquitoes in Makassar City during November 2017 until January 2018.